1989
DOI: 10.1055/s-0038-1646557
|View full text |Cite
|
Sign up to set email alerts
|

Risks to the Fetus of Radiologic Procedures Used in the Diagnosis of Maternal Venous Thromboembolic Disease

Abstract: SummaryThe diagnosis of suspected venous thromboembolic disease during pregnancy is problematic because of the fear of fetal irradiation with routine diagnostic procedures. In order to develop rational guidelines, we have calculated levels of radiation exposure to the fetus for the common diagnostic procedures and conducted a literature review to examine the fetal risks associated with these levels of radiation. A small increase in the relative risk of childhood cancer is suggested by a literature review of ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
96
0
14

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(110 citation statements)
references
References 37 publications
(47 reference statements)
0
96
0
14
Order By: Relevance
“…The association of thrombotic cerebral events and inherited thrombophilia is still controversial. Several studies have reported that patients with prothrombin or FV Leiden mutations are at higher risk of developing cerebral vein thrombosis [151,154,187]. However, other studies have failed to show a significant link between thrombophilia and the occurrence of cerebral venous or arterial thrombosis [1,145,146,152,[154][155][156]188] No studies have described the association between thrombophilia and cerebral ischemic events during pregnancy.…”
Section: Arterial Thrombosis During Pregnancymentioning
confidence: 93%
See 2 more Smart Citations
“…The association of thrombotic cerebral events and inherited thrombophilia is still controversial. Several studies have reported that patients with prothrombin or FV Leiden mutations are at higher risk of developing cerebral vein thrombosis [151,154,187]. However, other studies have failed to show a significant link between thrombophilia and the occurrence of cerebral venous or arterial thrombosis [1,145,146,152,[154][155][156]188] No studies have described the association between thrombophilia and cerebral ischemic events during pregnancy.…”
Section: Arterial Thrombosis During Pregnancymentioning
confidence: 93%
“…The resistance can also be acquired during the second and third trimester of a normal pregnancy as a result of increases in FV and factor VIII and decreased protein S levels [1,155,148,157]. The precise mechanism for this "physiological" APCR is still not known, nor its contribution to the higher risk of VTE during pregnancy [1,154,148,158]. The prothrombin mutation is associated with elevated plasma prothrombin levels (factor II activity >130 percent) and is present in about 2-5 percent of healthy individuals.…”
Section: Hereditary Thrombophilias and Venous Thrombosis During Pregnmentioning
confidence: 99%
See 1 more Smart Citation
“…Se a suspeita clínica é alta, mas os testes não invasivos são negativos para TVP, a venografia limitada com proteção abdominal que resulta em exposição feral < 0,05 rads deve ser considerada 11 . Se o resultado do US é duvidoso (pequena área de não compressibilidade), a venografia ou a RNM devem ser solicitadas.…”
Section: Os Testes Diagnósticos Podem Ser Não Invasivos (Ultrassom [Uunclassified
“…Computed tomographic (CT) venography can be a useful adjunct in suspected iliac vein thrombosis in non-pregnant patients, but it carries much higher radiation exposure for the foetus than conventional venography and should therefore be avoided during pregnancy [72,73].…”
Section: Conventional and Ct Venographymentioning
confidence: 99%